The Effect of Gold & Carbon Screen-Printed Electrode (SPE) for Biosensing Application by Electrochemical Method - Salamon Ali Rizal, Muhammad Nadiy; Mustafa, Prof. Ts. Dr. Mohd Kamarulzaki (Enhanced Knowledge in Sciences and Technology, 2023)
This study mainly characterized the aptamer-based biosensor as a straightforward and sensitive biosensor that work on the idea of aptamer-antigen interaction. By observing the morphologies, charge transfer, impedance, potential, and current on the carbon and gold screen-printed electrode (SPE) using the electrochemical technique and scanning electron microscope (SEM), the characteristic of the aptamer-based biosensor is examined. This work provides the result of cyclic voltammetry of carbon and gold Screen Printed Electrode (SPE), the analysis of immobilization of five biochemical solutions (Aptamer resuspension buffer, aptamer folding buffer, aptamer reducing buffer, thiol-modified aptamer and BSA) and chronoamperometry of different concentrations of hCG antigens. Experiments were conducted using Metrohm Autolab Potentiostat and on gold and carbon SPE. The polarization resistance (Rp) significantly decreases for each fabrication stage which means the SPE was stable and conductive to be used as a biosensor due to redox reactions (2.41k Ω, 79.8 Ω, 24.5 Ω). The polarization resistance (Rp) of an electrochemical process is inversely proportional to the current flowing. Changes in the diffuse layers of the analyte on the working electrode produce changes in the currents. The detection of hCG antigens in a wide range of concentrations as low as 0.1 ng/ml was achieved. Based on the data obtained, the electrochemical method proved the high specificity and sensitivity of the aptamer-based on gold screen-printed electrode compared to carbon.